Chronic Pelvic Inflammation Diminished Ovarian Reserve as Indicated by Serum Anti Mülerrian Hormone - Cui, Linlin (PLoS One, 2016)
OBJECTIVE: To explore the potential damaging effect of chronic pelvic inflammation on ovarian reserve. DESIGN: Case-control study. PATIENTS: A total of 122 women with bilateral tubal occlusion, diagnosed by hysterosalipingography (HSG) and 217 women with normal fallopians were recruited. MEASUREMENTS: Serum anti-Mullerian hormone (AMH), basic follicle-stimulating hormone (FSH), luteining hormone (LH), estradiol (E(2)), and testosterone (T) were measured; and antral follicle counts (AFCs) were recorded. RESULTS: Significantly lower level of AMH was observed in women with bilateral tubal occlusion compared to control group [2.62 (2.95) ng/ml vs. 3.37 (3.11) ng/ml, P = 0.03], and the difference remained after adjustment of BMI (P(adjust) = 0.04). However, no statistical difference was found in the levels of FSH [7.00 (2.16) IU/L vs. 6.74 (2.30) IU/L], LH [4.18 (1.52) IU/L vs. 4.63 (2.52) IU/L], E(2) [35.95 (20.40) pg/ml vs. 34.90 (17.85) pg/ml], T [25.07±11.46 ng/dl vs. 24.84±12.75 ng/dl], and AFC [6.00 (4.00) vs. 7.00 (4.00)] between two groups (p>0.05). CONCLUSIONS: Women with bilateral tubal occlusion showed decreased AMH level, suggesting that chronic pelvic inflammation may diminish ovarian reserve. More caution should be paid when evaluating the detriment of PID on female fertility.